157k views
1 vote
7x - 6 = 3 + x - 5 - 2x

User Alla
by
5.1k points

2 Answers

1 vote

Answer:

0

Explanation:

We need to factor the GCF (Greatest Common Factor).

The resulting term is a product of the GCF and the original expression divided by the GCF.

In our example, the GCF is equal to X + 2.

I'm not sure if its 0

But mine is "0"

User Niconoe
by
5.2k points
5 votes

Answer:

x=1/2

Explanation:

7x−6=3+x−5−2x

Step 1: Simplify both sides of the equation.

7x−6=3+x−5−2x

7x+−6=3+x+−5+−2x

7x−6=(x+−2x)+(3+−5)(Combine Like Terms)

7x−6=−x+−2

7x−6=−x−2

Step 2: Add x to both sides.

7x−6+x=−x−2+x

8x−6=−2

Step 3: Add 6 to both sides.

8x−6+6=−2+6

8x=4

Step 4: Divide both sides by 8.

8x /8 = 4 /8

x= 1 /2

User Aarbor
by
5.1k points